Jinghua Weikang capsule for helicobacter pylori eradication: A systematic review and meta-analysis with trial sequential analysis - Zhao, Qian; Wang, Wen-jia; Zhou, Shui-ping; Su, Jing; Sun, He; Zhai, Jing-bo; Hu, Yun-hui (Frontiers in Pharmacology, 2022)
Background: Helicobacter pylori (H. pylori) infection is one of the most common chronic bacterial infections worldwide. The resistance of H. pylori to antibiotics may increase the risk of treatment failure. Complementary and alternative regimens are still needed. This study aimed to critically assess the efficacy and safety of Jinghua Weikang capsule (JWC) for H. pylori eradication. Materials and Methods: PubMed, Embase, Web of Science, Cochrane library, China National Knowledge Infrastructure, Wanfang Digital Periodicals, and Chinese Science and Technology Periodicals database were searched from inception to April 2022. Randomized controlled trials (RCTs) comparing a combination of JWC and conventional treatments with conventional treatments alone or combined with placebo for H. pylori eradication were considered for inclusion. The primary outcome was H. pylori eradication rate. The meta-analysis and trial sequential analysis (TSA) were conducted if possible. Results: A total of 34 studies were included for the statistical analysis. A pooled result showed that JWC with the duration of 2 weeks combined with the triple/quadruple therapy could significantly increase the H. pylori eradication rate compared with the triple/quadruple therapy alone (RR: 1.13, 95% CI: 1.05 to 1.21, P = 0.0008). However, the evidence of benefit was not confirmed by TSA. Another pooled result showed that JWC with the duration of 4 weeks combined with the triple/quadruple therapy could significantly increase the H. pylori eradication rate compared with the triple/quadruple therapy alone (RR: 1.21, 95% CI: 1.15 to 1.27, P < 0.00001). The evidence of benefit was confirmed by TSA. There were no statistically significant differences in the incidence of adverse reactions between two groups. Conclusions: The present study suggests that JWC with the duration of 4 weeks can significantly improve the H. pylori eradication rate, and should be considered as a complementary treatment to conventional regimens for H. pylori eradication. However, more high-quality RCTs are still needed to confirm these findings.